Análise dos fatores comuns na dinâmica regional da pobreza - Moreira, Larisse Maria Ferreira (2019)
The present study uses the multilevel latent factor model in order to capture common shocks that may influence the national and/or local poverty scenario, which is measured by the indices proposed by Foster, Greer and Thorbecke (1984). Four national factors were then identified, and after identification, we performed three tests with the following purposes: to verify the size of national factors to explain state indicators; to verify if these national factors have any relation with macroeconomic variables; and what would be the conditions for the influence of national factors on regional ones. As a result of these tests we realize that states react to national factors differently, showing no pattern in the performance of poverty rates, demonstrating that local factors also have a strong influence on poverty. We also obtained as a result that national factors presented more significant results in the severity-related poverty index, and less significant results in the poverty-related index. We can also suggest that, in terms of the severity of poverty, national factors influenced state indicators on variables related to policies to combat illiteracy, the conditional cash transfer program (Bolsa Família) and the labor market.